Small supernumerary marker chromosomes in prenatal diagnosis—molecular characterization and clinical outcomes - Joksic, Ivana; Toljic, Mina; Milacic, Iva; Stankovic, Andjela; Karadzov Orlic, Natasa; Mikovic, Zeljko (Frontiers in Genetics, 2024)
Small supernumerary marker chromosomes (sSMCs) are infrequent findings in prenatal diagnostics, however they pose a great challenge for prenatal genetic counseling.We report prenatal 12 sSMC cases detected in a single center during 10 years period, their molecular characterization by fluorescence in situ hybridization (FISH) or chromosomal microarray (CMA). Those cases were found among 9620 prenatal diagnostic analyzes by GTG-banding technique. In selected cases, additional UPD testing was also done.Incidence of sSMCs in our study was 0.12%. sSMC characterization was done by FISH in 9 cases, in the remainder of three CMA was employed. The most common sSMC shape was centric minute, followed by inverted duplication and one case with ring conformation. sSMCs originating from acrocentric chromosomes (chromosomes 14, 21 and 22), sex chromosomes (X, Y) and non-acrocentric autosomal chromosomes (chromosome 4 and 18) were confirmed in 3 cases each; no result could be obtained in 3 further cases. No anomalies were detected by prenatal ultrasound in any of the cases. In 58% of the cases, outcome was reported as normal at birth, while anomalies at birth were described in one case. Only two patients opted for pregnancy termination. Preterm labor occurred in case of twin pregnancy resulting in stillbirth and early neonatal death of twins.Overall, our study highlights the importance of a sSMC characterization by molecular cytogenomic methods in order to make appropriate genotype-phenotype correlations and ensure adequate genetic counseling.